The phantom patrol - Benn, James R. (Benn, James R. Billy Boyle World War II mystery., 2024)
"Months after the Liberation of France, ex-Boston cop Billy Boyle has landed in its war-torn capital city, still carrying with him the weight of his last mission. He witnesses a Paris ailing from the carnage it has endured-blocked roadways, buildings marked by bullet holes--but with the nascent hope that the war might be coming to its end. When Billy and his long-time comrade Kaz survive a tense shoot-out in the Père Lachaise Cemetery, they discover a rare piece of artwork left behind in an unmarked grave. Could the artwork be connected to the Syndicat du Renard, a shadowy network of Nazi sympathizers known to be smuggling stolen artwork out of France? Billy's investigation takes him through a shadowy underworld of art thieves and the heroic squad of cultural protectors, like the real-life Monuments Men, trying to stop them. Trailing the Syndicat and its unknown leader, the Fox, Billy discovers that someone with a high level of security and communications clearance--someone in the Phantom regiment of the British Army--may be using his position to aid the thefts. Determined to stop the gang of looters, Billy heads up to the frontlines of the war, to a tense, frostbitten calvary, where the Phantom unit's headquarters is based. There, the Battle of the Bulge--one of the bloodiest campaigns in the history of World War II--unfurls in the Ardennes Forest, on the border of Belgium and Luxembourg. Can Billy and his team survive the bracing onslaught, and return a throng of stolen artwork to its rightful owners?"--